Probation staff experiences of managing suicidal and self-harming service users. (June 2015) - Mackenzie, Jay-Marie; Cartwright, Tina; Beck, Amy; Borrill, Jo
The current study sought to explore the impact of suicidal behaviours on probation staff, in relation to their experiences of working with probation service users who have carried out suicide, attempted suicide or self-harm. Thirteen in-depth interviews were carried out with probation staff who had direct contact with probation service users in one probation area, and had varying degrees of experience of managing suicidal or self-injurious service users. These were analysed using thematic analysis and five themes were identified. Findings indicate that staff felt that suicide and self-harm by service users are serious issues which need to be recognized and dealt with in an effective yet compassionate manner. Not attending the suicide prevention training, or lack of experience, were perceived as restricting their ability to know how to deal with these individuals, and offer support. Furthermore, staff were emotionally affected by these incidents and it is recommended that they should continue to be provided with access to appropriate support services after an incident.